Diagnostic competence of future educator-psychologists in a University environment: nature and structure. (Journal of Educational Sciences, 2017)
The article along with the issue of competence and competence approach in education discusses the concept of “diagnostic competence” in the aspect of preparation of different specialists in the sphere of education: from teacher to social worker. Also describes the initial stages of the experimental work for the study and development of diagnostic competence of future teachers-psychologists. Analysis of the obtained data allows suggesting that especially among students it is necessary to form readiness for diagnostic activities, the need for knowledge on psycho-pedagogical diagnosis, a positive attitude towards diagnostic activities that will be the basis for the development of diagnostic competence of future teachers-psychologists.After analyzing the sources, considering the diagnostic competencevarious representatives of the education sector, the author discussed the study and development of the required competencies in the University environment, in order to high-quality professional training of future teachers-psychologists.Theoretical analysis and initial practical experience of solving problems (the first stage of experimental work showed that for successful execution of increasingly complex tasks of the modern school and the educational psychologist requires deliberate reconstruction of all types of its future activities, furtherdevelopment of diagnostic competence in the context of the educational process, promoting professional and personal improvement of future specialists.
Keywords: competence approach in education; diagnostics; professional competence; diagnostic competence; the diagnostic component of the future professional activity